2007
DOI: 10.1098/rsbl.2007.0192
|View full text |Cite
|
Sign up to set email alerts
|

Twin intromittent organs ofDrosophilafor traumatic insemination

Abstract: In several animals, male genitalia create insemination wounds in areas outside the genital orifice of females. I report that such traumatic insemination (TI) occurs in the Drosophila bipectinata complex (Diptera: Drosophilidae) and illustrate a previously unknown evolutionary pathway for this behaviour. Flash fixation of mating pairs revealed the dual function of the paired claw-like basal processes, previously misidentified as a bifid aedeagus: (i) penetration of the female body wall near the genital orifice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
171
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(179 citation statements)
references
References 20 publications
6
171
1
1
Order By: Relevance
“…It is therefore also possible that sexually antagonistic interactions or adaptive postmating responses may have contributed to the decline in female cell density. As females experience copulatory wounding [45], haemocytes may be sequestered for wound repair and so removed from general circulation. In contrast to these trends in cell number, the age- [14] dependent decline in phagocytic activity of cells occurred at similar rates in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore also possible that sexually antagonistic interactions or adaptive postmating responses may have contributed to the decline in female cell density. As females experience copulatory wounding [45], haemocytes may be sequestered for wound repair and so removed from general circulation. In contrast to these trends in cell number, the age- [14] dependent decline in phagocytic activity of cells occurred at similar rates in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these spines, by breaching the female body wall during copulation, inflict wounds to the female (Kamimura 2007), as in the C. maculatus beetles noted above. Additionally, it has been claimed that sperm are injected into the female reproductive tract across the female body wall via the wound sites, thereby bypassing the female's genital orifice (Kamimura 2007), the usual route of sperm transfer in Drosophila.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been claimed that sperm are injected into the female reproductive tract across the female body wall via the wound sites, thereby bypassing the female's genital orifice (Kamimura 2007), the usual route of sperm transfer in Drosophila. Thus, the current view being promulgated is that the genital spines in D. bipectinata and related Drosophila species function in an unusual and extreme mode of sperm delivery: traumatic insemination (Kamimura 2007;Bonduriansky et al 2008;Ř ezáč 2009). In the present study, we demonstrate that the spines in D. bipectinata promote copulatory success, and not insemination or fertilization, contrary to the post-insemination sexual selection hypothesis for genital trait function and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In many species, the act of copulation (Kamimura 2007) and exposure to compounds in male seminal fluid reduce female survival and fecundity (Chapman et al 1995;Arnqvist & Nilsson 2000). It is not clear why males express traits that harm their sexual partners (Johnstone & Keller 2000;Lessells 2005).…”
Section: Introductionmentioning
confidence: 99%